Multi‐scale analysis of a migrating submarine channel system in a tectonically‐confined basin: The Miocene Gorgoglione Flysch Formation, southern Italy. Issue 1 (2nd July 2018) - Casciano, Claudio I.; Patacci, Marco; Longhitano, Sergio G.; Tropeano, Marcello; McCaffrey, William D.; Di Celma, Claudio
Abstract: The Miocene Gorgoglione Flysch Formation records the stratigraphic product of protracted sediment transfer and deposition through a long‐lived submarine channel system developed in a narrow and elongate thrust‐top basin of the Southern Apennines (Italy). Channel‐fill deposits are exposed in an outcrop belt approximately 500 m thick and 15 km long, oriented oblique to the palaeoflow, which was roughly south‐eastward. These exceptional exposures of channel‐fill strata allow the stacking architectures and the evolution of the channel system to be analyzed at multiple scales, enabling the effects of syn‐sedimentary thrust tectonics and basin confinement on the depositional system development to be deciphered. Two end‐member types of elementary channel architecture have been identified: high‐aspect‐ratio, weakly‐confined channels, and low‐aspect‐ratio, incisional channels. Their systematic stacking results in a complex pattern of seismic‐scale depositional architectures that determines the stratigraphic framework of the deep‐water system. From the base of the succession, two prominent channel complex sets have been recognized, namely CS1 and CS2, consisting of amalgamated incisional channel elements and weakly‐confined channel elements. These channelized units are overlain by isolated incisional channels, erosional into mud‐prone slope deposits. The juxtaposition of different channel architectures is interpreted to have been governed by regional thrust‐tectonics, in combination with a high subsidence rate that promoted significant aggradation. In this scenario, the alternating 'in sequence' and 'out of sequence' tectonic pulses of the basin‐bounding thrusts controlled the activation of coarse‐clastic inputs in the basin and the resulting stacking architectures of channelized units. The tectonically‐driven confinement of the depositional system limited the lateral offset in channel stacking, preventing large‐scale avulsions. This study represents an excellent opportunity to analyze the stratigraphic evolution of a submarine channel system in tectonically‐active settings from an outcrop perspective. It should find wide applicability in analogous depositional systems, whose stratigraphic architecture has been influenced by tectonically‐controlled lateral confinement and associated lateral tilting.